“La producción y comercialización de la leche y su incidencia en el desarrollo socio económico de la parroquia san juan, cantón Riobamba periodo 2015.” - Malca Yumi, Sonia Verónica (2017)
The present investigation was carried out in the parish of San Juan Canton Riobamba, Province of Chimborazo, the majority of the population is engaged in the activity of livestock and agriculture, which is a source of income for rural development, for this reason was determined that the production and commercialization of milk affects socio-economic development in the 2015 period. The present investigative work is divided by four chapters the same as detailed below Chapter I In this chapter, the Reference Framework was developed, which includes the problem statement, problem formulation, research objectives, and justification. Chapter II Therefore, in this chapter the Theoretical Framework was developed, which consists of units, as well as hypothesis, variables (independent, dependent) and the operationalization of the variables Chapter III refers to the Methodological Framework, which consists of methods, type of research, design of research, techniques and research instruments for data collection, processing of results and testing of the hypothesis. Chapter IV It consists of the conclusions and recommendations that is established at the end of the investigation.